Development of Enhanced Cloud File Sharing Security with eID Token-Based Trust Mechanisms - Umang Chaudhary; Ayan Rajput (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Numerous systems provide users an electronic identification (eID) for document signing or online service authentication (e.g., governmental eIDs, OpenID). Current solutions, however, fail to provide adequate methods for using them as conventional ID cards that digitally verify their holders to another individual in the actual realm. We foresee a comprehensive mobile eID that offers this capability while safeguarding privacy, meets the stringent security standards for governmental identities (such as driver’s licenses and passports), and is applicable in the private sector (e.g., as loyalty cards). This study delineates possible applications for a flexible and privacy-preserving mobile eID and examines the notion of privacy-preserving attribute searches. Additionally, we delineate essential functional, mobility, security, and privacy needs, and provide a concise review of alternative methodologies to address each of them.